Peranan Perancang Peraturan Perundang-Undangan Dalam Pembentukan Peraturan Daerah - Ida Ayu Dyah Permata Dewi; Ida Ayu Putu Widiati; I Ketut Sukadana (Jurnal Analogi Hukum, 2020)
Local Government has the rights to enfore each local provisions and other acts to exercise autonomy and co-administration duty. In each phases of the drafting of legislation, it involves the drafter of such legislation. The problem in this article is regarding the position and the duty of a drafter during the drafting of a local legislation as well as the implementation of the participation of a drafter in drafting of local legislation in the province of Bali. This research uses empirical legal research method. The result of this research shows that the position and duty of a drafter of a legislation in the drafting of local legislation is very important, namely to prepare, process, and formulate the draft of legislation and other legal instruments. Moreover, the implementation of the participation of the legislative drafters in the drafting of local legislation in the province of Bali, there are still 3 Districts or Cities which have not involve a drafter in the drafting of local legislation. The comparison of revoked legislation from the year 2013-2018 between Districts or Cities which do involve drafters and the Districts or Cities which do not involve a drafter shows a significant gap of numbers. However in the year 2018, the implementation of the drafters' involvement in the drafting of local legislation in the provincr of Bali is starting to be involved from the beginning to the final phase. Therefore the implementation of the drafters' involvement is starting to proceed effectively. The legal effect of not involving drafters explicitly, no legislation has clearly sanctioned such situasion, hence, there is an empty norm in this case. Pemerintah Daerah berhak menetapkan peraturan daerah dan peraturan perundang-undangan lain untuk melaksanakan otonomi dan tugas pembantuan. Dalam setiap tahapan pembentukan peraturan perundang-undangan mengikutsertakan perancang peraturan perundang-undangan. Permasalahan dalam penelitian ini adalah mengenai kedudukan dan tugas perancang dalam pembentukan perda serta pelaksanaan keikutsertaan perancang dalam pembentukan perda di Provinsi Bali. Penelitian hukum ini menggunakan metode empiris. Hasil penelitian menunjukkan bahwa Kedudukan dan Tugas Perancang Peraturan Perundang-undangan dalam Pembentukan Peraturan Daerah sangat penting yaitu menyiapkan, mengolah, dan merumuskan rancangan peraturan perundang-undangan dan instrumen hukum lainnya. Sedangkan Pelaksanaan Keikutsertaan Perancang Peraturan Perundang-undangan Dalam Pembentukan Peraturan Daerah Di Provinsi Bali, masih terdapat 3 Kabupaten atau Kota yang belum melibatkan perancang dalam pembentukan perda. Perbandingan jumlah perda yang dicabut dari tahun 2013-2018 antara Provinsi atau Kabupaten yang melibatkan perancang dengan Kabupaten atau Kota yang belum melibatkan perancang tidak menunjukkan perbandingan jumlah angka yang signifikan. Akibat hukum apabila tidak mengikutsertakan perancang secara ekplisit, peraturan perundang-undang tidak mencantumkan secara tegas mengenai sanksi sehingga terdapat norma kosong dalam hal ini.